Long-term outcome of photodynamic therapy with hexyl aminolevulinate, 5-aminolevulinic acid nanoemulsion and methyl aminolevulinate for low-risk Basal Cell Carcinomas - M. Salmivuori; M. Grönroos; T. Tani; J. Räsänen; E. Snellman; N. Neittaanmäki (Photodiagnosis and Photodynamic Therapy)
Background: Non-surgical treatments are cost-effective options for low-risk basal cell carcinomas (BCCs) i.e. superficial or small nodular BCCs located outside the high-risk locations. Hexyl aminolevulinate (HAL) and 5-aminolevulinic acid nanoemulsion (BF-200 ALA) with enhanced penetration depth enables the use of lower concentrations compared to methylaminolevulinate (MAL) in photodynamic therapy (PDT). We have previously reported comparable short-term efficacies for MAL 16 %, BF-200 ALA 7.8 % and HAL 2 % in PDT of low-risk BCC, and here we report the long-term results. Objectives: The goal of this trial was to compare long-term outcomes of HAL and BF-200 ALA, compared to MAL in PDT of low-risk BCCs. Methods: Ninety-eight histologically verified low-risk BCCs on the trunk or extremities were included and randomized into three arms to receive PDT in two sessions with MAL, BF-200 ALA or HAL. A blinded dermatologist assessed the response, cosmetic outcome, and obtained biopsies for histological verification at three months, one year and five years. Histologically verified non-responsive lesions were excised. Patients’ satisfaction with the treatment was also queried. Results: According to intention-to-treat (ITT) analyses, the cumulative response rate at one year was 90.6 % for MAL, 81.3 % for BF-200 ALA, and 75.8 % for HAL, and correspondingly at five years 71.9 %, 54.6 % and 60.6 %. There were no statistically significant differences between interventions and comparator. The overall cumulative response rate for PDT was 82.5 % at one year and 62.2 % at five, and 48.6 % of the treatment failures were recorded at five years. The recurrent lesions were excised as second line treatment. No aggressive subtypes were reported, with only superficial or nodular growth in the final histopathological report. There were no significant differences in cosmetic outcome or patient satisfaction. Conclusions: This trial shows that HAL has potential for dermatological PDT. However, the long-term efficacy of PDT in the treatment of low-risk BCCs remains rather low.